Las Tareas Complementarias Planificadas Y Su Relación Con La Construcción Del Conocimiento Y El Proceso De Creación De Hábitos De Estudio En Los Alumnos De La Carrera De Ingeniería En Contabilidad Y Auditoría De La Universidad Técnica De Babahoyo. - MORA ARISTEGA, JULIO ERNESTO (2014)
This Research Is Based On The Application Of Complementary Tasks Applied In The Learning Process Of Students Engineering In Accounting And Auditing Of The Technical University Of Babahoyo, And Consists Of Several Points: First, An Introduction, An Overview Of The Topic, Then The Research Topic Arises, The Context Of The Research Described, Then The Entire Presentation Of The Problem Situation Is Made, Which Is Defined By The Setting Of A General Problem And Specific Problems. Then Presented Temporal, Spatial Delimitation And Observation Units Used, Justification Setting Out The Reasons For Running The Research Process, After Objectives That Are Directly Related To The Problem Posed. The Theoretical Framework Formed: Background Research, Referential Framework And Theoretical Position; Covers Concepts, Theories And Studies Already Conducted On The Topic Of Thesis. Research Hypotheses Which Were Put To The Test Are Presented, And The Analysis Of The Data Presented By Tables, Charts And Graphs That Allow Better Appreciate The Work And Generate Conclusions And Recommendations Of The Process. An Alternative Proposal Of Application In Which Steps Are Suggested To Be Implemented To Improve The Process Of Applying Complementary Tasks And independent work. In the thirteenth point is presented the literature and the last point are presented the annexes.